Characterisation of the Endophytic and Rhizospheric Bacillus licheniformis Strains Isolated from Sweet Potato with Plant Growth-Promoting and Yield Enhancing Potential - Ádám Bordé-Pavlicz; Anuar Rysbekovich Zhumakayev; Henrietta Allaga; Mónika Vörös; Pramod Wasudeo Ramteke; Tamás Monostori; Csaba Vágvölgyi (Advances in Agriculture)
The primary aim of the present study was to identify bacterial isolates with yield-enhancing potential for application as biofertilisers in the cultivation of sweet potato. Therefore, endophytic and rhizospheric strains were isolated from sweet potato plantations in Hungary to identify bacterial strains with plant growth-promoting and antifungal potential. In total, seven Bacillus licheniformis strains were identified and subjected to detailed ecophysiological investigations. Experiments have been conducted to investigate the tolerance of selected strains to different limiting factors such as pH, temperature, and water activity, which affect survivability in various agricultural environments. The majority of tested B. licheniformis strains exhibited plant growth-promoting potential (e.g., production of indole-3-acetic acid up to 40.42 μg mL−1, production of ammonia up to 0.87 mg mL−1, phosphorus solubilising activity, siderophore production), with two strains (SZMC 27713 and SZMC 27715) demonstrating inhibitory activity (ranging between 7% and 38%) against plant pathogenic fungi prevalent in sweet potato cultivation. Furthermore, strain SZMC 27715 induced accelerated germination and a significantly higher germination rate in tomato seeds compared to the control. In a field study, it was observed that strain SZMC 27715 had a potent yield enhancing effect in sweet potato, where a significant yield per plant increase was observed in all treatments (1.13, 1.09 and 1.40 kg) compared to the control plants (0.92 kg). The highest yield per plant was observed when the cuttings were soaked combined with two additional foliar treatments. To the best of our knowledge, this is the first report of the successful utilisation of the B. licheniformis strain as a biofertiliser for yield enhancement in sweet potato cultivation. Based on our results, strain SZMC 27715 has potential for application as a biofertiliser in sweet potato cultivation either as a standalone option or in a microbial consortium.